Promoted ABA Hydroxylation by Capsicum annuum CYP707As Overexpression Suppresses Pollen Maturation in Nicotiana tabacum - Kim, Hyun Min; Park, Se Hee; Ma, Sang Hoon; Park, Seo Young; Yun, Chul-Ho; Jang, Geupil; Joung, Young Hee (Frontiers in Plant Science, 2020)
Abscisic acid (ABA) is a key signaling molecule that mediates plant response to stress. Increasing evidence indicates that ABA also regulates many aspects of plant development, such as seed germination, leaf development, and ripening. ABA metabolism, including ABA biosynthesis and degradation, is an essential aspect of ABA response in plants. In this study, we identified four cytochrome P450 genes (CaCYP707A1, 2, 3, and 4) that mediate ABA hydroxylation, which is required for ABA degradation in Capsicum annuum. We observed that CaCYP707A-mediated ABA hydroxylation promotes ABA degradation, leading to low levels of ABA and a dehydration phenotype in 35S::CaCYP707A plants. Importantly, seed formation was strongly inhibited in 35S::CaCYP707A plants, and a cross-pollination test suggested that the defect in seed formation is caused by improper pollen development. Phenotypic analysis showed that pollen maturation is suppressed in 35S::CaCYP707A1 plants. Consequently, most 35S::CaCYP707A1 pollen grains degenerated, unlike non-transgenic (NT) pollen, which developed into mature pollen grains. Together our results indicate that CaCYP707A mediates ABA hydroxylation and thereby influences pollen development, helping to elucidate the mechanism underlying ABA-regulated pollen development.